(untitled) (Bangladesh Journal of Animal Science, 2013)
Data on 3637 cows of seven genetic groups at Baghabarighat milk shed area during the period from 1991 to 2000 were analyzed. The genetic groups were Pabna Milking (PM) cows, ½PM×½ Sahiwal (PM×SL), ½PM×½Friesian (PM×FN), Australian Friesian Sahiwal (AFS), ½Sahiwal×¼PM×¼ Friesian [SL(PM×FN)], ½Friesian×¼PM×¼Sahiwal [FN(PM×SL)] and ½Friesian×¼Sahiwal×¼Jersey [FN(SL× JR)]. The purpose of this study was to estimate genetic trends of some dairy traits (birth weight, lactation yield, fat% and SNF %). The heritability values were estimated as 0.27±0.05 for birth weight, 0.45±0.03 for lactation yield, 0.37±0.04 for fat% and 0.46±0.01 for SNF %. The genetic trends for the dairy traits were computed as average of breeding values using all data for cows born during 1991- 2000. It was observed that the genetic trend of birth weight of calves increased in PM×SL, PM×FN, AFS and FN(SL×JR) at the rate of 0.08, 0.10, 0.12 and 0.05 kg per year, respectively. The same for lactation yield of genetic group PM×FN, AFS, SL(PM×FN) and FN (SL×JR) rose up at the rate of 6.78, 5.20, 4.14 and 5.19 liters per year, respectively. The genetic group PM, PM×SL and PM×FN showed negative trend for fat % at the rate of 0.0005, 0.002 and 0.004% per year, respectively. But the same increased in AFS, SL(PM×FN), FN(PM×SL) and FN(SL×JR) at the rate of 0.002, 0.013, 0.011 and 0.004% per year, respectively. The genetic trend of SNF % in only one group showed negative trend in PM×SL at the rate of 0.01 % per year. On the contrary, PM, PM×FN, AFS, SL(PM×FN), FN(PM×SL) and FN (SL×JR) increased at the rate of 0.005, 0.010, 0.011, 0.0002, 0.014 and 0.003% per year, respectively. The high genetic variability of birth weight, lactation yield, fat and SNF% indicated that there are good opportunities for genetic improvement when including these traits in a selection scheme. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14103 Bang. J. Anim. Sci. 2012. 41 (2): 67-73